A hybrid technique using minimal spanning tree and analytic hierarchical process to prioritize functional requirements for parallel software development - Muhammad Yaseen, Muhammad Yaseen; Mustapha, Aida; Shah, Muhammad Arif; Ibrahim, Noraini (Springer, 2023)
Software for large enterprises such as the enterprise resource planning (ERP) is more likely to be developed by a team of software developers where the functional requirements (FRs) are distributed in parallel developers. Therefore, development of pre-requisite FRs must be carefully timed to see which requirement is to be implemented frst by assigning priority to some FRs over others, so that FRs can be made available on time to parallel developers. This research proposes a hybrid prioritization technique of minimal spanning trees (MST) and AHP called the spanning analytic hierarchical process (SAHP) for FRs prioritization by exploiting MST capability to prioritize large size software FRs with smaller pairwise comparisons but with more consistent results. Using Numerical Assignment (NA) technique, prioritized FRs from SAHP are assigned to priority groups such that top-priority groups contain high-priority FRs and low-priority groups contain low-priority FRs. low-priority group of FRs are dependent on high-priority groups. As a result, within each priority group, inter-dependencies in FRs are reduced for parallel developers. The proposed technique is evaluated on FRs of ODOO ERP and the results showed that SAHP reduces estimation time of parallel developers as compared to AHP and other techniques.